A Copper‐Catalyzed Multicomponent Reaction and 'Click Strategy' for the Stereoselective Synthesis of a New Series of Oxazolone Peptidomimetics with α‐Acylamino Amide and β‐Amido Ketone Structures. Issue 12 (December 2013) - Balan, Biny; Bahulayan, Damodaran
Abstract A novel 'click ligation' strategy for the stereoselective synthesis of a medium‐size library of structurally complex and functionally diverse oxazolone peptidomimetics, which contain α‐acylamino carboxamide or β‐amido ketone residues, is presented. Most of these molecules have lipophilicity constant values (log P) in the qualifying range for cell permeability, and that indicates the possibilities of these new molecules to be used in the search for potential inhibitors for a broad spectrum of enzymes.